Phasen, Zustandswechsel und die einfache Phasensemantik - Engerer, Volkmar P. (Tidsskrift for Sprogforskning, 2008)
Taking a preliminary periodization of phasal verb research as a starting point, the article argues for an implicit connection between four historical phases of research and five features of grammatical description of phasal verbs. The remainder of the contribution focuses on one period, in particular the formal semantic approaches inspired by Montague grammar in the late 1970s, with David Dowty as the perhaps most prominent figure. The article shows that early formal semantics is characterised by interpreting the most basic feature in phasal verb grammar, Simple Phasal Semantics (SPS), as a change-of-state concept. This move establishes phasal meaning as a basic feature in lexicon structure, and, in consequence, characterises phasal verbs as lexicalisations of overall semantic features. To substantiate this analysis, the essentials of SPS are presented, followed by a discussion of Dowty’s conception of change-of-state in his reanalysis of Vendler’s four aspectual verb classes in English.